Determination of rational parameters of chemical transesterification technology of sunflower oil - Korchak, Mykola; Корчак, Микола; Shostia, Anatolii; Шостя, Анатолій; Usenko, Svitlana; Усенко, Світлана; Floka, Liudmyla; Флока, Людмила; Hniti, Nadiia; Гнітій, Надія; Morozova, Liubov; Морозова, Любов; et al. (Private Company Technology Center, 2024)
The object of the study is the process of chemical transesterification of sunflower oil. Liquid vegetable oils are an important component in the products of chemical, cosmetic, paint, food and other industries. Among other oils, sunflower oil is of exceptional industrial importance. Chemical transesterification technology is used to obtain oils, fats and their mixtures with specified properties required for various industries. An important task is to develop rational conditions for the oil transesterification process using a highly efficient and safe catalyst. The process of chemical transesterification of refined deodorized frozen sunflower oil according to DSTU 4492 (CAS Number 8001-21-6) using potassium glyceroxide was studied. The original oil has the following parameters: peroxide value 0.2 ½ O mmol/kg, acid value 0.1 mg KOH/g, moisture mass fraction 0.03 %, crystallization temperature –18.38 °С. The effect of transesterification parameters on the oil crystallization temperature was examined. The catalyst concentration in all experiments was 0.45 % by weight of the oil. The oil crystallization temperature was determined by differential scanning calorimetry. Rational parameters of oil transesterification were defined: temperature 110 °C, duration 1.5 hours. Under these conditions, there is a maximum increase in the oil crystallization temperature (up to –4.1 °С). The effectiveness of the rational oil transesterification parameters was confirmed by changes in the triglyceride composition by chromatography analysis. The obtained rational conditions for the chemical transesterification of sunflower oil in the presence of the potassium glyceroxide catalyst can also be used in the processes of oil transesterification with other raw materials using this catalyst. Об’єктом дослідження є процес хімічної переетерифікації соняшникової олії. Рідкі рослинні олії є важливою складовою продукції хімічної, косметичної, лакофарбової, харчової та інших галузей промисловості. Серед інших олій виняткове промислове значення має соняшникова олія. Технологія хімічної переетерифікації використовується для отримання масел, жирів і їх сумішей із заданими властивостями, необхідними для різних галузей промисловості. Важливим завданням є розробка раціональних умов процесу переетерифікації нафти з використанням високоефективного та безпечного каталізатора. Досліджено процес хімічної переетерифікації олії соняшникової рафінованої дезодорованої вимороженої згідно з ДСТУ 4492 (номер CAS 8001-21-6) з використанням гліцероксиду калію. Вихідна олія має такі показники: перекисне число 0,2 ½ О ммоль/кг, кислотне число 0,1 мг КОН/г, масова частка вологи 0,03 %, температура кристалізації –18,38 °С. Досліджено вплив параметрів переетерифікації на температуру кристалізації олії. Концентрація каталізатора в усіх дослідах становила 0,45 % маси масла. Температуру кристалізації олії визначали методом диференціальної скануючої калориметрії. Визначено раціональні параметри переетерифікації олії: температура 110 °С, тривалість 1,5 години. За цих умов спостерігається максимальне підвищення температури кристалізації олії (до –4,1 °С). Ефективність раціональних параметрів переетерифікації олії підтверджена зміною тригліцеридного складу за допомогою хроматографічного аналізу. Отримані раціональні умови хімічної переетерифікації соняшникової олії в присутності каталізатора гліцероксиду калію можуть бути використані також у процесах переетерифікації олії з іншою сировиною з використанням цього каталізатора.
Визначення раціональних параметрів технології хімічної переетерифікації соняшникової олії
Милостивий Роман Васильович https://orcid.org/0000-0002-4450-8813
Keywords: oil crystallization temperature; температура кристалізації олії; chemical transesterification of sunflower oil; хімічна переетерифікація соняшникової олії; potassium glyceroxide catalyst; каталізатор гліцероксид калію